Biological Traits Of Fungal Pathogens Affecting Bulb Flowers And Methods Of Control. (Eurasian Journal of Research, Development and Innovation, 2024)
The experiments were carried out in floriculture farms located in Namangan region during 2017-2019 years, and laboratory work was carried out at floriculture centers in Namangan region of the Republic of Uzbekistan. 19 species and 5 forms of fungal pathogens were detected in 7 species of bulb flowers grown in the Namangan regions of the Republic of Uzbekistan